Simultaneous Anterior Glenohumeral Dislocation and Ipsilateral Acromioclavicular Separation: A Dual Injury of the Shoulder - Kılıçaslan, Ömer Faruk (Cureus, 2017)
Isolated acromioclavicular separations or shoulder dislocations are common injuries. However, a combination of complete acromioclavicular separation and anterior shoulder dislocation is extremely rare. Herein we present a combination of anterior shoulder dislocation and type III acromioclavicular separation that was succesfully treated conservatively. Orthopaedic surgeons should have a high clinical suspicion in daily practice. We believe that both pathologies can be treated conservatively.